Manajemen Pendamping Program Keluarga Harapan di Desa Cadasari Kecamatan Cadasari Kabupaten Pandeglang - Sanjaya, Sanda; Sholih, Sholih; Fauzi, Ahmad (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of effective management in the implementation of the Family Hope Program (Program Keluarga Harapan, PKH) to achieve its goals optimally, particularly at the grassroots level, such as in Cadasari Village, Cadasari Subdistrict, Pandeglang Regency. The objective of this study is to analyze the implementation of PKH companion management, which includes the stages of planning, execution, evaluation, and the challenges encountered in the mentoring process. A descriptive method with a qualitative approach was used, with data collected through observation, interviews, and documentation. The findings reveal that the management of PKH mentoring in Cadasari Village has been carried out in accordance with the stages of management. In the planning phase, the number of aid recipients was adjusted to the official criteria, although some eligible low-income families were not accommodated due to central government quota limitations. In response, the village government monitored families whose economic conditions had improved for immediate graduation from the program, allowing room for other, more deserving families to benefit. Program implementation followed procedures set by the central government, with a focus on empowerment and welfare improvement. Regular evaluations were conducted to assess the program’s effectiveness, and the results served as a basis for decision-making, including the reallocation of aid to more appropriate beneficiaries. This study demonstrates that structured and adaptive management of PKH mentoring enhances the accuracy of aid distribution and strengthens program governance at the village level.